PENGARUH SERTIFIKASI GURU, PROFESSIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU DISEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 1 PEUREULAK DAN SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 2 PEUREULAK KABUPATEN ACEH TIMUR - M. Daud (Universitas Islam Islam Sumatera Utara, 2020)
Meeting these demands requires a variety of learning competencies. Y = 14,689 + 0.309X1 + -0.92X2 + 0.482X3. The performance value of State Vocational High School 1 Peureulak District Teacher in East Aceh 2019 is 14,689, in which the value of the certification, professionalism and motivation variables is ignored. The equation above explains that the regression coefficient X1 (certification) has a positive value of 0.309, this shows that the certification variable has a positive influence on the performance of the State Vocational High School 1 Peureulak 1 East Aceh District Teacher 2019. If teacher certification increases 1% , then the teacher's performance will increase by 3.09. Regression coefficient X2 (professionalism) also has a positive value of 0.92, this shows that the variable has a positive influence on the performance of Teachers of Public Vocational High School (SMK) 1 Peureulak, East Aceh District. professionalism increased by 1%, the teacher's performance did not increase as seen results n-9.2 this is caused by the professionalism carried out by the teacher not related to the level of professionalism of the teacher while at school because there are still many certified teachers who have not yet run the process teaching and learning professionally this is in line with research found.